2005
DOI: 10.1175/jhm419.1
|View full text |Cite
|
Sign up to set email alerts
|

Year-to-Year Variations of the Stable Isotopes in Precipitation in February at Cuiabá, Located on the Northern Fringe of Pantanal, Brazil

Abstract: Large year-to-year variations of δ18O were found in the precipitation recorded in the International Atomic Energy Agency/Global Network of Isotopes in Precipitation (IAEA/GNIP) database for February at Cuiabá, located on the northern fringe of Pantanal, Brazil. Three depleted years (1963, 1978, and 1968) and three enriched years (1966, 1984, and 1983) were chosen to investigate this phenomenon and to correlate the amount of precipitation, the occurrences of storm precipitation, and the vapor flux field. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
3
0
1
Order By: Relevance
“…Inclinations of these lines are close to 8, indicating a low evaporation effect; the interception is about 12-13 for most stations, probably due to effects of vapour recirculation along the transportation of air masses. For the Cuiabá station, the interception is about 7, this value could be associated with the proximity of this station to the moisture source located in the Amazonian region, as observed by Matsuyama et al [29].…”
Section: Monthly Recordlocal Meteoric Water Linessupporting
confidence: 69%
See 1 more Smart Citation
“…Inclinations of these lines are close to 8, indicating a low evaporation effect; the interception is about 12-13 for most stations, probably due to effects of vapour recirculation along the transportation of air masses. For the Cuiabá station, the interception is about 7, this value could be associated with the proximity of this station to the moisture source located in the Amazonian region, as observed by Matsuyama et al [29].…”
Section: Monthly Recordlocal Meteoric Water Linessupporting
confidence: 69%
“…Evaluation of temporal variations in isotopic composition of precipitation collected at Cuiabá GNIP station, located in the Brazilian central zone, has revealed that during the active period of the SACZ, more depleted values observed in precipitation were associated with the precipitation amount and the occurrence of storm precipitation, while during the inactive period of the SACZ, a weakening of the vapour flux coming from the Amazon basin was observed [28,29].…”
Section: Precipitation and Stable Isotopes Over Brazilmentioning
confidence: 99%
“…Precipitation rates have been found to influence isotopic composition during the monsoonal seasons, and are suggested as one cause of the amount effect [e.g., Matsuyama et al , 2005; Vuille et al , 2005]. Table 1 shows significant negative relationships between wet season δ D values and GPCP daily rainfall rates for all regions.…”
Section: Local Controls On Isotopic Compositionmentioning
confidence: 99%
“…Such water balance tracer approaches typically involve the analysis of stable water isotopes (Gibson et al 1993). Isotopic analysis of water has proven to be one of the most important tools for investigating the water budget of water bodies (Matsuyama et al 2005) and is indispensable for water balance studies in fairly inaccessible areas (Turner and Townley 2006). Insight into lake hydrological processes can be gained even with only a small number of samples (Rozanski et al 2000).…”
mentioning
confidence: 99%